THE DYNAMICS OF COMMUNITY EMPOWERMENT IN TOURISM: A CASE IN NUSA PENIDA ISLAND, BALI - Suardana I Wayan; Ariani Ni Made; Kristianto Yohanes (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2021)
Community empowerment is not only seen from an economic aspect, but can be studied in a behavioral perspective. Poverty and community empowerment will be enhanced if individual behavior changes. The survey was conducted purposively on 250 people of Nusa Penida and analyzed with SEM. The results found that 85% of the people of Nusa Penida have transformed the tourism sector. The emergence of several attractions in the Nusa Penida region, as well as the support of traditional institutions in the capital motivates people to get out of poverty. Community attitudes mediate cultural relations and community empowerment. Attitudes of wanting to change from habits of inferiority, laziness, and just relying on the help of others will provide reinforcement to the empowerment of the community. The community has social capital and a strong entrepreneurial spirit to break free from poverty. Tourism has proven to be an antecedent in growing the attitude and empowerment of the Nusa Penida community. Local entrepreneurs have sprung up in various tourism activities, such as lodging, transportation and water recreation businesses. The success of other people becomes a challenge that motivates themselves to reduce the negative culture existing in society.